Предмет: Алгебра,
автор: vlvmelnikov007
Розв’яжіть рівняння (3х + 4)(4х – 3) – 5 = (2х + 5)(6х – 7).
Ответы
Автор ответа:
1
(3х + 4)(4х – 3) – 5 = (2х + 5)(6х – 7)
12х^2 - 9x + 16x - 12 - 5 = 12x^2 - 14x + 30x - 35
- 9x + 16x - 12 - 5 = -14x + 30x - 35
7x - 16x = 17 - 35
-9x = -18
x = 2
Ответ: 2
Автор ответа:
2
Похожие вопросы
Предмет: Русский язык,
автор: чеченка8
Предмет: Русский язык,
автор: RomanLexik1
Предмет: Русский язык,
автор: POMOGITE771
Предмет: Геометрия,
автор: 123451823
Предмет: Английский язык,
автор: Аноним